The Eastern Mediterranean Sea mean sea level decadal slowdown: the effects of the water budget - Borile, Federica; Pinardi, Nadia; Lyubartsev, Vladyslav; Ghani, Mahmud Hasan; Navarra, Antonio; Alessandri, Jacopo; Clementi, Emanuela; Coppini, Giovanni; Mentaschi, Lorenzo; Verri, Giorgia; da Costa, Vladimir Santos; Scoccimarro, Enrico; et al. (Frontiers in Climate, 2025)
This paper analyses the decadal variability of the Mean Sea Level (MSL) trend for the Mediterranean Sea and three subregions using a combination of satellite altimetry, tide gauges and reanalyses datasets for the past 30 years (1993–2022). These estimates indicate a decadal variability of the MSL across the analysed period, and a trend slowdown in the 2013–2022 decade compared to previous periods. While the overall trend remains positive across the Mediterranean basin, regional differences are evident. The Western Mediterranean shows an accelerating trend, consistent with global sea level rise, while the Eastern Mediterranean has experienced a decadal slowdown, particularly in the semi-enclosed Adriatic and Aegean Seas, where negative trends are observed. This slowdown is attributed to the combined effects of changes in the water cycle and the balancing of thermal and haline steric components. A key driver of this trend is increased evaporation, which is not offset by precipitation, runoff, or transport through the Straits. These results underscore the significance of the Mediterranean’s water budget in influencing sea level trends and highlight the complexity of modelling and interpreting decadal sea level changes. The findings suggest that continued monitoring and a better understanding of regional water budgets are crucial for refining future projections and developing effective climate adaptation strategies for the Mediterranean coastal areas.